Evaluation of the effects of soil structure interaction on a multistorey rc building. (December 2020) - Deepashree, R; Kavitha, S; Mamatha, P G; Vishal, B V
Abstract: when a structure undergoes seismic excitation, the displacement caused in the structure and the ground are not independent of one another, this dependency of each other causes noticeable changes in the structure. In order to study this interdependency, a phenomenon called soil structure interaction (SSI) comes into existence which is been neglected during design process but omitting it leads to unsafe design. Henceforth it's important to consider the effect of SSI although its effect is negligible for buildings that are low rise. In the current study 6 models of G+13 multi-storey symmetrical RC building with storey height 3m is modelled using ETABS which is assumed to be located in Hard-soil, Medium-soil and Soft-soil of zone-IV is subjected to response spectrum analysis. The structure is analysed without SSI and also the behaviour of the structure is studied by considering SSI effect using spring elements. The variation of systematic parameters such as storey displacement, storey drift, Storey shear, base-shear, natural period, Storey stiffness and overturning moment has been studied and compared. It is observed that response of the structure is higher under SSI condition and soft soil is more critical, it's important to consider the effects of SSI during design process.